Dimensions of supervisory communication and organizational commitment: a case study of a Malaysian organization - Mohamad, Bahtiar; Abu Bakar, Hassan (Fakulti Komunikasi dan Bahasa Moden, Universiti Utara Malaysia, 2004)
This research attempts to test the relationship between supervisory communication and organizational commitment based on a Malaysian organization setting. Further tests were conducted to identify which supervisory communication behavior will be a significant predictor of organizational commitment. Two hundred and thirty one (231) respondents from a large semi-government corporation and its subsidiary in Northern Peninsular Malaysia were involved in this study. It reveals that there is significant positive relationship between superior-subordinate communication and organizational commitment. Further analysis indicates that negative relationship communication and job-relevant communication are significant predictors of organizational commitment.